2019
DOI: 10.1002/lno.11343
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of Humboldt squid, Dosidicus gigas, in conjunction with body size and climatic variability in the Gulf of California, Mexico

Abstract: Over the past two decades, the Gulf of California (GOC) has experienced three strong El Niño events ), each of which was followed by a drastic reduction in mantle length of mature Humboldt squid, Dosidicus gigas (from >60 cm to <20 cm). However, it is unclear how the oceanographic changes associated with strong El Niño events affected the midwater organisms on which D. gigas feed, limiting our ability to assess the relative importance of temperature and food availability in the phenotypic response of D. gigas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…Cololabis saira (Tian, Akamine & Suda, 2003), albacore tuna Thunnus alalunga (Zainuddin, Saitoh & Saitoh, 2004), tropical crab Gecarcoidea natalis (Shaw & Kelly, 2013), and O. bartramii in the Pacific Ocean (Chen, Zhao & Chen, 2007), have strong linkages with the ENSO events. For D. gigas, previous studies have stated that the ENSOinduced sudden temperature change possibly caused biological change (individual growth, forage community and population structure) during its 1-year short life history (Keyl, Argüelles & Tafur, 2011;Arkhipkin et al, 2015;Portner et al, 2019). Furthermore, our studies demonstrated that habitat quality (suitability and range) and spatial distribution of D. gigas showed high correlations with the ENSO index.…”
Section: Enso Types Yearsupporting
confidence: 67%
“…Cololabis saira (Tian, Akamine & Suda, 2003), albacore tuna Thunnus alalunga (Zainuddin, Saitoh & Saitoh, 2004), tropical crab Gecarcoidea natalis (Shaw & Kelly, 2013), and O. bartramii in the Pacific Ocean (Chen, Zhao & Chen, 2007), have strong linkages with the ENSO events. For D. gigas, previous studies have stated that the ENSOinduced sudden temperature change possibly caused biological change (individual growth, forage community and population structure) during its 1-year short life history (Keyl, Argüelles & Tafur, 2011;Arkhipkin et al, 2015;Portner et al, 2019). Furthermore, our studies demonstrated that habitat quality (suitability and range) and spatial distribution of D. gigas showed high correlations with the ENSO index.…”
Section: Enso Types Yearsupporting
confidence: 67%
“…On the other hand, due to the typical feeding behaviors of squid, the number of crustaceans was hard to precisely assess. Therefore, the occurrences of crustacean prey were represented based on presence or absence (Portner et al, 2019).…”
Section: Dietary Analysismentioning
confidence: 99%
“…Several studies demonstrated that they can respond quickly to environmental change, such as abnormal warm surface temperatures and decreased prey availability, due to plasticity in life-history strategy. For example, environment-driven switch in distribution, size-at-maturity, and prey selectivity may allow D. gigas to rapidly cope with El Niño events, resulting in unpredictable interannual fluctuations in population size and biomass (Zeidberg and Robison, 2007;Hoving et al, 2013;Portner et al, 2019). However, given the large-scale distribution of D. gigas, knowledge of their trophic niche divergence and ecological diversification is still incomplete.…”
Section: Introductionmentioning
confidence: 99%